Deformation and recrystallization of interstitial free (IF) steel - Duggan, B.; Tse, Y.; Lam, G.; Quadir, Md Zakaria (Springer, 2011)
The rolling texture of Body Centered Cubic (BCC) low carbon and interstitial free (IF) steel consists of two crystallographic fibers, the a fiber («110»//RD) and the ? fiber ((«111»/ /ND). Cells, subgrains, and microbands, where these are not associated with significant lattice curvature, provide the driving forces for recrystallization. However, when these microstructures are associated with significant short range lattice curvature, as they are in deformation or shear bands, they can provide the nucleation sites. The process of recrystallization in IF steel is shown to occur in two stages: the first where the nuclei are contained in the original rolled-out grains belonging to the ? fiber, and where the essential lattice curvature is derived from shear and deformation bands. The second stage involves the impingement/coalescence of several recrystallized grains in the as-rolled envelope of an original hot band grain which provides a super-nucleation event, in which the as rolled boundaries bow out to give an equiaxed microstructure. An elegant proof is provided for this process, along with a simple model based on Strain Induced Boundary Migration (SIBM). The well-known optimal cold rolling, beyond which the drawability is known to degrade, is explained by deformation banding of a particular subset of the grains belonging to the a fiber. Finally, a novel experiment is described, based on the observed deformation banding behavior of crystals belonging to the ? fiber, which leads to very strong ? recrystallization textures, which are desirable in deep drawing.